Survei Motivasi Atlet Dalam Mengikuti Program Latihan di Klub Bolavoli Se Karisidenan Kediri - Utama, Rendy Ramanda Sandika (Ilmu Olahraga, 2021)
Motivation is important for athletes in participating in training programs, because motivation is a concept that explains the reasons for someone to behave and as encouraging someone to do something to achieve the goals they want to achieve, with the great motivation of athletes in following training programs will achieve optimal success of the training program. The purpose of this study was to determine the level of motivation of athletes in participating in training programs at the Volleyball Club in Karisidenan Kediri. This research is a descriptive quantitative approach. The population of this study were all athletes in Karisidenan Kediri including athletes in the Volleyball Club in Tulunggagung, Blitar, Kediri City and Kediri Regency, with a sample size of 77 athletes and the sampling technique was quota sampling technique. The instrument in this study used a validated questionnaire. Descriptive quantitative data analysis techniques. The results of this study indicated that 66% of the athletes' intrinsic motivation in participating in the training program at the volleyball club was moderate. Meanwhile, 57% of the athletes' extrinsic motivation in participating in the training program at the volleyball club was moderate. From these results it can be concluded that intrinsic motivation is more dominant than extrinsic motivation in influencing the learning motivation of athletes in participating in training programs at the Volleyball Club in Karisidenan Kediri.